2001
DOI: 10.1002/pros.1062
|View full text |Cite
|
Sign up to set email alerts
|

Human rhabdosphincter cell culture: A model for videomicroscopy of cell contractions

Abstract: These results demonstrate that cholinergic stimulation triggers contraction of cultured human rhabdosphincter cells. This model might help to understand external urethral sphincter physiology and to establish new therapies for the treatment of sphincter dysfunctions. Prostate 47:189-193, 2001.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Primary cell culture was established using the half‐dry method modified from a previously established protocol . RS cell culture is rare with only one publication in this area . Briefly, RS tissues were cut into 1 × 1 mm 2 pieces and placed into the bottom of 25 cm 2 flasks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary cell culture was established using the half‐dry method modified from a previously established protocol . RS cell culture is rare with only one publication in this area . Briefly, RS tissues were cut into 1 × 1 mm 2 pieces and placed into the bottom of 25 cm 2 flasks.…”
Section: Methodsmentioning
confidence: 99%
“…23 RS cell culture is rare with only one publication in this area. 24 Briefly, RS tissues were cut into 1 × 1 mm 2 pieces and placed into the bottom of 25 cm 2 flasks. Culture flasks containing 2 mL of medium were placed upside-down in a 5% CO 2 incubator at 37°C for 2 h to allow the tissues to attach.…”
Section: Primary Rs Cell Culturementioning
confidence: 99%
“…Electrophysiological studies on human RS cells were performed in primary cell cultures. Biopsies were taken from the prostatic part of the RS [6,13]. Subsequently, the small amounts of striated muscle cells were collected under microscopic control.…”
Section: L-and T-type Ca 2þ Channel Currents In Human Rs Cellsmentioning
confidence: 99%
“…In order to investigate the potential of this new therapy, it is necessary to analyze the cellular properties of myoblasts taken from the RS and skeletal muscle (SKM) in more detail. Corvin and coworkers reported [13] that striated muscle fibres that are capable to contract upon application of agonists can be obtained from explant cultures grown from prostatectomy and cystoprostatectomy specimens. Their data suggest that the human RS contains progenitor cells as other SKM (also called satellite cells, see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the LUT, cultures of urethral, urinary bladder and ureter cells have been reported, but pharmacology remains largely uncharacterized (e.g. Baskin et al ., 1993; Kropp et al ., 1999; Corvin et al ., 2001). Organ bath studies of ureter, urethra and more common urinary bladder have been reported and the reader is referred to representative examples (Levin et al ., 1995; Pontari et al ., 2004; Su et al ., 2004; Wheeler et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%